2021
DOI: 10.21315/mjms2021.28.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of COVID-19-Related Deaths Among Older Adults in Malaysia

Abstract: In response to the rising number of COVID-19-related deaths among older adults in Malaysia, observation concerning COVID-19-related mortality among older adults is of urgent public health importance. This study presents a review of the COVID-19-related death cases among older adults in Malaysia. Clinical and social demographic data of death cases officially released by the Ministry of Health Malaysia were reviewed. As of 12 June 2020, 81 older adult death cases were identified and included in this study. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…It is also important to explore if this group of people are more likely to have experienced difficulties in access or negative interactions with health and mental health providers in primary care. Previous research has reported that lower level of education was associated with a more negative evaluation of primary care in Brazil and Malaysia [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to explore if this group of people are more likely to have experienced difficulties in access or negative interactions with health and mental health providers in primary care. Previous research has reported that lower level of education was associated with a more negative evaluation of primary care in Brazil and Malaysia [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the home deaths were reported by older patients while younger patients reported in-transit deaths. [14][15][16] Earlier studies reported that older persons preferred home care rather than hospital care. 16 This might be one reason for high death counts in older patients but the reasons for in-transit deaths in younger age group require further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Satu kajian mengenai faktor risiko kematian pada pesakit COVID-19 dewasa menunjukkan bahawa kira-kira 50% pesakit tua yang meninggal berusia 70 tahun atau ke atas. Sebaliknya pesakit yang lebih muda menunjukkan gejala biasa, seperti demam, batuk dan dyspnoea (Mat Din et al, 2021). Bagi pesakit yang sembuh, sama ada pesakit muda atau tua kesembuhan dihubungkaitkan dengan ketahanan rohani dan bagaimana daya tahan ini membantu pesakit melawan sakit yang dialami.…”
Section: Pengenalanunclassified